Model-Based Systems Engineering Capabilities to Connect Descriptive and Analytic Model: Case Studies Hybrid Propulsion of Electric Aircraft - Zulkarnain, Muhammad Fikri; Nurprasetio, Ignatius Pulung; Mulyanto, Taufiq; Pasaribu, Hisar Manongam (BRIN Publishing, 2024)
Model-based Systems Engineering (MBSE) is a system development framework that utilizes the formalization of modeling to support systems engineering processes beginning early in the system development stage. This research aim is to explore and evaluate the implementation of the MBSE tool chain, especially in descriptive-analytic capabilities, traceability, ease of design customizations, and ease of making changes. MBSE processes, including requirements definition, functional decomposition, physical decomposition (architecture), and analysis were performed using a case study. The case study is the design and analysis of several hybrid propulsion configurations for electric aircraft. The ease of change and modification is shown by the process of adding, removing, and rerouting system elements and connections to modify from one configuration to another. Analysis has been performed by modeling the analysis context via the SysML Block Diagram, the interconnection of value via the SysML Parametric Diagram, and the calculation and results via the Cameo Instance Table. The result of the proposed propulsion model in SysML for full electric configuration has similar results to reference, while the results for hybrid propulsion have similar trends compared to other studies without MBSE. The method to compare analysis results and requirements with Measure of Performances (MoPs) as mediators has been proposed and performed